2018
DOI: 10.1007/s00535-018-1518-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of the treatment outcome in patients with advanced biliary tract cancer receiving gemcitabine plus cisplatin as first-line chemotherapy

Abstract: Background Few studies have clearly identified the prognostic factors in patients with advanced biliary tract cancer (BTC) receiving gemcitabine plus cisplatin (GC) which is acknowledged as standard chemotherapy regimen. Objectives The aim of this study was to identify predictive factors of the overall survival (OS) in advanced BTC patients receiving GC therapy. Methods Data of 307 patients with advanced BTC who received GC therapy as the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 42 publications
2
22
1
Order By: Relevance
“…Chronic inflammation was reported to play an important role in the development and progression of BTC. NLR or dNLR are inexpensive markers reflecting the host inflammation and were validated in the current and the previous studies [22,26,29].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Chronic inflammation was reported to play an important role in the development and progression of BTC. NLR or dNLR are inexpensive markers reflecting the host inflammation and were validated in the current and the previous studies [22,26,29].…”
Section: Discussionmentioning
confidence: 63%
“…Ishimoto et al reported 77 patients with pure iCCA and observed that lactate dehydrogenase (LDH), C-reactive protein (CRP), and CEA levels were significantly associated with OS in the multivariate analysis [21]. Suzuki et al analysed 307 patients and identified poor ECOG performance status, elevated serum LDH, and elevated NLR as independent unfavourable prognostic factors [22]. Salati et al illustrated NLR, ECOG performance status, CA19-9 and the prognostic nutritional index (PNI), an indicator derived from serum albumin and peripheral lymphocyte count, were prognostic factors for OS in patients undergoing first-line chemotherapy of platinum/gemcitabine combination [23].…”
Section: Discussionmentioning
confidence: 99%
“…10,11 In the literature, several clinical and biochemical factors have been described as prognostic factors in ABC, such as Eastern Cooperative Oncology Group performance status (ECOG PS), primary tumour location, disease status, number of metastatic sites, haemoglobin, bilirubin, LDH and neutrophil-to-lymphocyte ratio. [12][13][14][15][16] Nevertheless, none of these has been convincingly validated and the power of single factors in predicting survival is limited. 17,18 Additionally, growing research interest is headed to novel biomarkers with potential predictive and prognostic value such as non-coding RNAs and exosomal proteins, [19][20][21] though this research field is still in its infancy.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Palliative chemotherapy is the standard treatment for recurrent, unresectable advanced or metastatic biliary tract cancer (ABC) resulting in median overall survival (mOS) hardly exceeding 12 months . In the literature, several clinical and biochemical factors have been described as prognostic factors in ABC, such as Eastern Cooperative Oncology Group performance status (ECOG PS), primary tumour location, disease status, number of metastatic sites, haemoglobin, bilirubin, LDH and neutrophil‐to‐lymphocyte ratio . Nevertheless, none of these has been convincingly validated and the power of single factors in predicting survival is limited .…”
Section: Introductionmentioning
confidence: 99%
“…Several risk factors correlated to overall survival (OS) have emerged in recent studies and led to different stratification approaches, including risk factors like primary tumour location, disease status, metastatic sites, Eastern Cooperative Oncology Group (ECOG) performance status (PS), and biochemical laboratory parameters [14][15][16][17][18]. Moreover, the immune system is increasingly recognized as important [19,20]: neutrophil, lymphocyte, or monocyte counts and their ratios functioned as predictors for median OS of patients suffering from ABC [14,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%